Multi-foci division of nonlinear energy absorption on ultrashort pulse laser singulation of sapphire wafers - Lye, Celescia Siew Mun (2022)
The multi-foci division of through thickness nonlinear pulse energy absorption on ultrashort pulse laser singulation of single side polished sapphire wafers has been investigated. Firstly, it disclosed the enhancement of energy absorption by the total internal reflection of the laser beam exiting from an unpolished rough surface. Secondly, by optimizing energy distribution between foci and their proximity, favorable multi-foci energy absorption was induced. Lastly, for effective nonlinear energy absorption for wafer separation, it highlighted the importance of high laser pulse energy fluence at low pulse repetition rates with optimized energy distribution, and the inadequacy of increasing energy deposition through reducing scanning speed alone. This study concluded that for effective wafer separation, despite the lower pulse energy per focus, energy should be divided over more foci with closer spatial proximity. Once the power density per pulse per focus reached a threshold in the order of 1012 W/cm2, with approximately 15 μm between two adjacent foci, wafer could be separated with foci evenly distributed over the entire wafer thickness. When the foci spacing reduced to 5 μm, wafer separation could be achieved with pulse energy concentrated only at foci distributed over only the upper or middle one-third wafer thickness.